Kualitas Pernikahan Pada Pasangan Muda di Pekanbaru: Penggunaan Media Sosial dan Kematangan Emosi - Herawati, Icha; Amita, Nindy; Rizal, Irfani (UIR Press, 2022)
Marriage is an interesting topic to discuss. Uniting two individuals who have different backgrounds, characteristics, and traits that are not the same is not easy in marriage. Divorce rates are always increasing every year making research on marriage is still growing. Today's young couples are young individuals who are active in using social media, so it is very possible that these activities affect household life, especially the marriage process. The purpose of this study was to see how the relationship between social media use and emotional maturity in young couples. This research is a survey research with a quantitative approach with a research scale distribution. The scale used is the scale of social media use and the emotional maturity scale. The research sample consisted of 266 respondents who were young married couples in Pekanbaru City. The results of this study indicate that there is a relationship between the use of social media and emotional maturity. The results of the analysis test using the Product Moment Technique obtained a coefficient value of -0.638 with a sig = 0.000 (p <0.05) so it can be concluded that there is a negative relationship between social media use and emotional maturity in young couples. It can be interpreted that high social media use is associated with low emotional maturity, and vice versa, low social media use is associated with high emotional maturity. Based on the results of the study, it was also found that the use of social media was high and emotional maturity was very low in the research subjects.